UPAYA PENINGKATAN KETERAMPILAN GURU DALAM PENERAPAN PEMBELAJARAN AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) BIDANG STUDI MATEMATIKA MELALUI KEGIATAN KELOMPOK KERJA GURU (KKG) MINI DI SD NEGERI136537 KOTA TANJUNGBALAI - Mailina Mailina (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
The results of the implementation of school action research that takes place in 3 research cycles can be concluded: 1) Training in the form of Mini KKG and guidance on the application of PAKEM approach has added to the understanding (insight) and skills of elementary teachers. State 136537 on the importance of implementing pakem approach in classroom learning; 2) The results of the analysis showed that training activities in the form of KKG Mi ni provided more knowledge for teachers about PAKEM approach materials, while the improvement of teacher skills in PAKEM pan-raisers in the classroom was more widely obtained.